Formation of Teams of Performers of Projects at Innovative Enterprises within the Framework of the «Industry 4.0» Concept - Ihor Matyushenko; Mariia Danova; Olena Feoktystova; Ruslan Melnyk (International Journal of Supply Chain Management, 2019)
The problem of human resource management in the planning and implementation of high-tech projects in innovative enterprises is considered. This problem arises in the conditions of the fourth industrial revolution, due to the need for effective implementation of projects using breakthrough technologies, since such projects require a special level of competence of contractors. The procedures for forming an expert commission for evaluating alternative options for the composition of teams of high-tech project performers are described, as well as the process of forming a collective decision in the form of conjunctive consensus. The methodological basis of the described process of collective expert assessment is based on the following tools known in the theory of variational calculus, such as: a – truncated middle calculus, excess ratio, statistics Q, the values selective average. An illustrative example is given of evaluating alternative options for the composition of the project for creating a new model of a self-propelled passenger ramp at a typical aviation profile enterprise